Hybrid intelligent systems : 23rd International Conference on Hybrid Intelligent Systems (HIS 2023), December 11-13, 2023. Volume 4, Machine learning applications - International Conference on Hybrid Intelligent Systems Olten, Switzerland ; Porto, Portugal ; Kaunas, Lithuania ; Noida, India ; Kochi, India ; Online) 2023; Bajaj, Anu; Mishra, Pooja Manghirmalani; Abraham, Ajith; Kahraman, Cengiz (Cham : Springer, 2025)
This book presents 48 selected papers focused on Machine Learning Based Solutions from the 23rd International Conference on Hybrid Intelligent Systems, which was held in five different cities namely Olten, Switzerland; Porto, Portugal; Kaunas, Lithuania; Greater Noida, India; Kochi, India and in online mode. The 23rd International Conference on Hybrid Intelligent Systems (HIS 2023) was focusing on synergistic combinations of multiple approaches to develop the next generation of intelligent systems. HIS 2023 had contributions by authors from 44 countries. This book offers a valuable reference guide for all industrial specialists, scientists, academicians, researchers, students, and practitioners in the field of machine learning and industrial applications.
Gifted by Professor Ajith Abraham
Includes author index.
Keywords: Artificial intelligence -- Congresses; Expert systems (Computer science) -- Congresses